Unstable osteochondral fracture of the talus, osteochondritis dissecans, and chronic lateral ankle instability in an adolescent athlete: a case report - Brooks, T. J.; Crawford, K.; Curry, E. E. (International Journal of Athletic Therapy & Training, 2022)
A 15-year-old multisport athlete with chronic left ankle pain and instability 2 years following initial injury was diagnosed with an unstable osteochondral fracture of the lateral talar dome, osteochondritis dissecans, and lateral ligament instability. The patient underwent open surgical repair consisting of loose body excision, lateral ligament reconstruction, and talar dome debridement and microfracture followed by postoperative therapeutic exercise for 7 months. The patient successfully returned to competitive sports within a calendar year. Although not considered particularly rare among adult populations, osteochondral fracture of the talus is relatively rare in adolescents. This case demonstrates that a diagnosis of unstable osteochondral fracture and/or gross lateral ligament instability should be considered in cases involving adolescent athletes with significant ankle injury and prolonged pain and/or loss of function.